2020
DOI: 10.3390/atmos11040418
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Takeoff Performance in a Changing Climate for Canadian Airports

Abstract: Temperature and wind are major meteorological factors that affect the takeoff and landing performance of aircraft. Warmer temperatures and the associated decrease in air density in future climate, and changes to crosswind and tailwind, can potentially impact aircraft performance. This study evaluates projected changes to aircraft takeoff performance, in terms of weight restriction days and strong tailwind and crosswind occurrences, for 13 major airports across Canada, for three categories of aircraft used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Very low temperature may increase the runway's slipperiness and undermine the planes' braking effectiveness (Nuijten, 2016). Another effect of extreme temperatures is the planes' maximum takeoff weights, which are affected by the changing air density due to humidity and temperature uctuations and are especially in uential for airports with higher altitudes and shorter runways (Zhao, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Very low temperature may increase the runway's slipperiness and undermine the planes' braking effectiveness (Nuijten, 2016). Another effect of extreme temperatures is the planes' maximum takeoff weights, which are affected by the changing air density due to humidity and temperature uctuations and are especially in uential for airports with higher altitudes and shorter runways (Zhao, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution and decay of aircraft wake vortices are closely related to the surrounding atmospheric conditions. Research has shown that wind disturbances can affect the propagation and dispersion of wake vortices [4]. In particular, vertical wind directly impacts the structure, vortex strength, decay rate, and altitude of the vortex core, which subsequently affects wake turbulence separation and the extent of the danger zone.…”
Section: Introductionmentioning
confidence: 99%
“…These models provide valuable insights into wake vortex characteristics, but they may have limitations when capturing all the complex interactions in real-world conditions [5,10]. 4.…”
mentioning
confidence: 99%
“…On airplanes, many phenomena occur. The condition when the plane takes off has a lot of big influences that play a role in the process (Bardera-Mora et al, 2019;Zhao and Sushama, 2020). Like the aerodynamics formula, an airplane requires lower pressure on the upper side and higher pressure on the lower side to fly.…”
Section: Introductionmentioning
confidence: 99%